Identification of QoI fungicide-resistant genotypes of the wheat pathogen Zymoseptoria tritici in Algeria - ALLIOUI, Nora; SIAH, Ali; BRINIS, Louhichi; REIGNAULT, Philippe; HALAMA, Patrice (Phytopathologia Mediterranea, 2016)
Septoria tritici blotch caused by Zymoseptoria tritici is currently one of the most damaging diseases on bread and durum wheat crops worldwide. A total of 120 monoconidial isolates of this fungus were sampled in 2012 from five distinct geographical locations of Algeria (Guelma, Annaba, Constantine, Skikda and Oran) and assessed for resistance to Quinone outside Inhibitors (QoI), a widely used class of fungicides for the control of fungal diseases of wheat. Resistance was screened using a mismatch PCR assay that identified the G143A mitochondrial cytochrome b substitution associated with QoI resistance. The isolates were QoI-sensitive, since all possessed the G143 wild-type allele, except for three isolates (two from Guelma and one from Annaba), which had fungicide resistance and possessed the A143 resistant allele. QoI resistance was confirmed phenotypically using a microplate bioassay in which the resistant isolates displayed high levels of half-maximal inhibitory azoxystrobin concentrations (IC50s) when compared to sensitive reference isolates. Genetic fingerprinting of all isolates with microsatellite markers revealed that the three resistant isolates were distinct haplotypes, and were are not genetically distinguishable from the sensitive isolates. This study highlights QoI-resistant genotypes of Z. tritici in Algeria for the first time, and proposes a management strategy for QoI fungicide application to prevent further spread of resistance across the country or to other areas of Northern Africa.